2023
DOI: 10.37394/23207.2023.20.78
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Work Life, Job Enrichment and their Impact on Employee Retention: Exploratory Research in Private Colleges in Baghdad

Abstract: Quality of work life (QWL) can be impacted by a variety of factors, including organizational structure, the physical environment, job security, and the opportunity for personal growth and development. As job enrichment is a key component of QWL, it can play an important role in employee retention. The main objective of this research is to determine the dimensions of QWL and job enrichment that promote employee retention and how those dimensions significantly impact employee retention. The research was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…However, an empirical study with a similar scale has been found in Peru without demonstrating its validity or reliability [63]. Various empirical investigations have used the QoWL scale, associating them with various variables [29,[64][65][66][67][68][69] and in different contexts. However, few publications have been found in databases applied to RBE.…”
Section: Discussionmentioning
confidence: 99%
“…However, an empirical study with a similar scale has been found in Peru without demonstrating its validity or reliability [63]. Various empirical investigations have used the QoWL scale, associating them with various variables [29,[64][65][66][67][68][69] and in different contexts. However, few publications have been found in databases applied to RBE.…”
Section: Discussionmentioning
confidence: 99%